Study on the Rheological Properties of Slate with Hard Structural Surface - Wang, Rui; Zhu, Mingli (International Journal of Natural Resources and Environmental Studies, 2025)
It is of important significance for the stability of rock engineering to research the non-linear characteristic of rock creep under high stress. The shear creep behavior experimental of slate with hard structural plane were done by using CSS-283 two-way universal testing machine, to analysis on the variation law of creep parameters with stress and time, and obtained the nonsteady parameters creep equation. By the comparison with the theory calculated results of the stationary and non-stationary models and the test results, the non-stationary viscoelastic rheological model is the more exactly reflect the rock viscoelastic deforming performance than the stationary viscoelastic rheological models.